(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Brushless DC motor is suitable for wide range of application in battery-powered vehicles, machine tools, robots, automatic wheelchairs, aerospace, temperature controllers and in many engineering, applications owing to their mechanical and electrical characteristics. Though, the non-linearity features of this motor drive make it problematic to operate it with a conventional Proportional integral derivative (PID) controller. To eliminate this problem, a Fuzzy Logic Controller with Gaussian membership function was designed. The controller is planned to record changes in speed references and steadies the output speed during load fluctuations. The usefulness of the projected technique is verified in this paper by developing mathematical simulation model in MATLAB Simulink software. The simulation results demonstrate that the proposed Fuzzy-Logic controller (FLC) illustrations a significant improvement of the control performance in comparison to the PID controller for both speed and load disturbance fluctuations.